1989
DOI: 10.1002/ajh.2830300104
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation studies in thrombotic thrombocytopenic purpura, with special reference to von willebrand factor and protein S

Abstract: The profile of blood coagulation and fibrinolysis was studied in detail in eight patients with acute thrombotic thrombocytopenic purpura (TTP). In the majority of the patients, fibrinogen, factor XIII, antithrombin III, alpha 2-plasmin inhibitor, plasminogen, and alpha 2-macroglobulin were normal, whereas FDP, plasmin-alpha 2-plasmin inhibitor complex, and tissue-type plasminogen activator antigen were marginally or moderately elevated. Low fibronectin values were observed in four patients. Protein C and C4b-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Although some patients with TTP have been reported to have low protein S antigen levels before treatment [11], venous thrombotic events are not typical features of TTP or its treatment with conventional PEX with FFP, and none of our patients had prior similar events. The level of FPS in all three patients fell to approximately that of the S/DP exchange fluid following repeated PEX and, as anticipated, there was rapid recovery of FPS to normal or near normal levels when PEX with CSP (which reportedly contains normal FPS levels) was instituted.…”
Section: Discussionmentioning
confidence: 60%
“…Although some patients with TTP have been reported to have low protein S antigen levels before treatment [11], venous thrombotic events are not typical features of TTP or its treatment with conventional PEX with FFP, and none of our patients had prior similar events. The level of FPS in all three patients fell to approximately that of the S/DP exchange fluid following repeated PEX and, as anticipated, there was rapid recovery of FPS to normal or near normal levels when PEX with CSP (which reportedly contains normal FPS levels) was instituted.…”
Section: Discussionmentioning
confidence: 60%
“…9,43,44 Our observation that the prevalence of the factor V Leiden allele in TM patients is increased in a subset of TM patients is consistent with previous studies that have implicated the thrombomodulin/protein C anticoagulant pathway in TM. Takahashi et al 34 reported low functional levels of protein S, and Glas-Greenwalt et al 35 observed low levels of protein C in some TM patients. Decreased protein S function has been reported to sensitize animals to the development of microvascular thrombosis in a model of E coli endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Reported abnormalities of coagulation proteins in TM include increased PAI-1 activity and deficiencies of protein C, protein S, tissue plasminogen activator, and urokinase-type plasminogen activator. [32][33][34][35] Studies in kindreds with familial HUS indicate that genetic alterations of complement factor H, a plasma protein that down-regulates complement activity, are prevalent in this subset of TM patients. [36][37][38][39] Complement activation is known to induce expression of tissue factor and adhesion molecules on endothelial cells and procoagulant alterations on platelet surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…If, as suggested, the abnormal multimer unit structure is the sign of a partially proteolyzed vWF [39], the chromatographic removal of this LMW species on DEAE-fractogel should be bene ficial to the recovery of a more functional purified vWF. Since in some reported cases of thrombotic thrombocyto penic purpura, a LMW-multimer fragment was found [43], the possible presence of a fainter LMW multimer in the purified vWF could mean a certain risk of thrombogenicity for the vWD patient. However, practically negli gible levels of proteolytic activity were measured in the vWF concentrate, and thrombin, PKA and kallikrein were undetectable.…”
Section: Discussionmentioning
confidence: 99%